Eksplorasi Dinamika antara Internet dan Kemiskinan Multidimensional di Indonesia: Pendekatan Kuasi-Eksperimental - Gunawan, Kleovan Nathanael (Jurnal Ekonomi Kependudukan dan Keluarga, 2025)
Poverty is a dynamic, diverse, and multidimensional concept. Its definition has evolved over time, moving from a monetary focus to a multidimensional perspective. Although poverty reduction has long been a critical issue, few studies have examined the role of the internet in addressing multidimensional poverty. To bridge this gap in the literature, this study explores the impact of internet access on multidimensional poverty in Indonesia, using data from the 2023 Susenas survey. Based on Propensity Score Matching results, evidence shows that internet access negatively affects multidimensional poverty. This research underscores the importance of internet access, highlighting the need for policies to address the digital divide.